Important Probiotics to Management of Urinary Tract Infections in Women: Probiotik Penting untuk Manajemen Infeksi Saluran Kemih pada Wanita - Ali Abd Kadhum (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Urinary tract infections (UTIs) are prevalent among women, often leading to repeated antibiotic treatment or surgical intervention, which increases healthcare costs. Specific Background: The rise of multidrug-resistant (MDR) bacteria complicates treatment strategies, necessitating alternative approaches to manage recurrent UTIs effectively. Knowledge Gap: Despite the documented benefits of probiotics in various health contexts, their role in preventing recurrent UTIs, particularly in regions like Nasiriyah City, remains inadequately explored. Aims: This study aimed to evaluate the efficacy of different probiotic strains (Lactobacillus rhamnosus, Lactobacillus reuteri, and Lactobacillus acidophilus) as adjuncts to conventional treatments in reducing UTI recurrence among women. Results: A total of 150 female participants were recruited, with 100 having a history of recurrent UTIs and 50 serving as a control group. The study revealed that Lactobacillus rhamnosus and Lactobacillus reuteri significantly reduced UTI recurrence rates compared to placebo, while Lactobacillus acidophilus demonstrated moderate efficacy. The analysis also indicated a high prevalence of antibiotic-resistant bacteria among UTI cases, highlighting the need for innovative treatment strategies. Novelty: This research uniquely contributes to the understanding of probiotic supplementation in UTI management, emphasizing the potential of Lactobacillus strains as effective preventative measures against recurrent infections. Implications: The study suggests incorporating probiotics, specifically Lactobacillus rhamnosus and Lactobacillus reuteri, into clinical practice to reduce antibiotic reliance and improve patient outcomes. Highlights: Probiotics reduce UTI recurrence rates effectively. High antibiotic resistance highlights need for alternatives. Consider probiotics as complementary therapy for better outcomes. Keywords: urinary tract infections, probiotics, Lactobacillus, multidrug-resistant bacteria, prevention